2007
DOI: 10.1107/s1600536807043553
|View full text |Cite
|
Sign up to set email alerts
|

4-(4-Chlorophenyl)-5-[2-methyl-1-(4-methylphenyl)-2-nitropropyl]-1,2,3-selenadiazole

Abstract: Key indicators: single-crystal X-ray study; T = 290 K; mean (C-C) = 0.005 Å; R factor = 0.044; wR factor = 0.102; data-to-parameter ratio = 16.4.In the title compound, C 19 H 18 ClN 3 O 2 Se, the heterocyclic ring makes dihedral angles of 40.74 (12) and 51.76 (11) with the chlorophenyl and methylphenyl rings, respectively. The molecular structure is stabilized by weak intramolecular C-HÁ Á ÁSe and C-HÁ Á ÁO interactions, and the crystal packing is stabilized by weak intermolecular C-HÁ Á ÁO interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(6 reference statements)
4
6
0
Order By: Relevance
“…The geometric parameters in the compound agree with the values of similar structures (Mellini & Merlino, 1976a;Mellini & Merlino, 1976b;Bertini et al, 1984;Gunasekaran et al, 2007). The phenyl ring makes a dihedral angle of 40.74 12 (Table 1; Cg is the centre of gravity of the heterocyclic ring).…”
Section: S1 Commentsupporting
confidence: 78%
See 1 more Smart Citation
“…The geometric parameters in the compound agree with the values of similar structures (Mellini & Merlino, 1976a;Mellini & Merlino, 1976b;Bertini et al, 1984;Gunasekaran et al, 2007). The phenyl ring makes a dihedral angle of 40.74 12 (Table 1; Cg is the centre of gravity of the heterocyclic ring).…”
Section: S1 Commentsupporting
confidence: 78%
“…For related literature see: Mellini & Merlino (1976a,b); Bertini et al (1984); El-Kashef et al (1986); El-Bahaie et al (1990); Kuroda et al (2001); Padmavathi et al (2002); Saravanan et al (2006). A similar compound with a chlorophenyl ring has been reported recently (Gunasekaran et al, 2007).…”
Section: Related Literaturementioning
confidence: 77%
“…For related literature, see: Mellini & Merlino (1976a,b); Bertini et al (1984); El-Kashef et al (1986); El-Bahaie et al (1990); Kuroda et al (2001); Padmavathi et al (2002); Saravanan et al (2006); A similar compound with a chlorophenyl ring has been reported by Gunasekaran et al (2007).…”
Section: Related Literaturementioning
confidence: 78%
“…The five-membered 1,2,3-selenadiazole moiety (C1/N1/N2/Se1/C2) of the title compound adopts a planar conformation as observed in the selenadiazole moieties of several crystal structures (Arsenyan et al, 2007;Saravanan et al, 2006a;Saravanan et al, 2006b;Saravanan et al, 2007;Saravanan et al, 2008;Marx et al, 2007;Marx et al, 2008a;Marx et al, 2008b;Gunasekaran et al, 2007a;Gunasekaran et al, 2007b). Cremer & Pople puckering analysis (Cremer & Pople, 1975) cannot be performed, for its weighted average absolute torsion angle is 0.89°, which is less than 5.0°.…”
Section: Related Literaturementioning
confidence: 94%
“…Considering the importances of the 1,2,3-selenadiazole derivatives, we present herein the single-crystal structure analysis of the title compound. The bond lengths of the 1,2,3-selenadiazole moiety in the title compound are comparable to those observed for selenadiazole moieties in several crystal structures such as 4-methyl-5-ethoxycarbonyl-1,2,3-selenadiazole phenylboronic acid (Arsenyan et al, 2007), diethyl 2-((4-methylphenyl)(4-phenyl-1,2,3-selenadiazol-5-yl)methyl)malonate (Saravanan et al, 2006a), 4-(4-chlorophenyl)-5-(1-(4-methoxyphenyl)-2-methyl-2-nitropropyl)-1,2,3-selenadiazole (Saravanan et al, 2006b), 3-(4-methylphenyl)-3-(4-(4-methylphenyl)-1,2,3-selenadiazol-5-yl)-2-phenylpropanenitrile , ethyl (Z)-3-(4-chlorophenyl)-2-cyano-3-(4-phenyl-1,2,3-selenadiazol-5-yl)prop-2-enoate (Saravanan et al, 2008), 5-(2-methyl-2-nitro-1-phenylpropyl)-4-phenyl-1,2,3-selenadiazole (Marx et al, 2007), 4-(4-Chlorophenyl)-5-(1-(4-chlorophenyl)-2-methyl-2-nitropropyl)-1,2,3-selenadiazole (Marx et al, 2008a), diethyl 2-((4-nitrophenyl)(4-phenyl-1,2,3-selenadiazol-5-yl)methyl)malonate (Marx et al, 2008b), 5-[2-methyl-1-(4-methylphenyl)-2-nitropropyl]-4-phenyl-1,2,3-selenadiazole (Gunasekaran et al, 2007a) and 4-(4-chlorophenyl)-5-[2-methyl-1-(4-methylphenyl)-2-nitropropyl]-1,2,3-selenadiazole (Gunasekaran et al, 2007b). The molecular structure of the title compound is shown in Fig.…”
Section: Related Literaturementioning
confidence: 99%